Peran Inovasi Produk Dan Jaringan Bisnis Cheese Cake Yang Diolah Menjadi Makanan Yang Populer - Resya Dwi Marselina; Cindy Oktavia; Dian Abadi; Tarisa Rahmawati; Yudi Permana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to develop and plan an effective business network for the cheese cake product innovation business, especially in building a business network so that the cheese cake business can continue to be popular. Observations in this research were carried out by observing consumer tastes and documentation was carried out by collecting data regarding effective business networks. The subject of this research is the development of product innovation businesses through business networks and the object is the Cheese Cake business. Based on the results of research on the development of product innovation and an effective business network for Cheese Cake, it can be concluded that the development of the cheese cake business can be carried out effectively if Cheese Cake can be marketed online so that it can be more widely known by the public by strengthening its innovation and business network